Testing the effectiveness of genetic monitoring using genetic non‐invasive sampling. Issue 1 (27th December 2021) - Schultz, Anthony James; Strickland, Kasha; Cristescu, Romane H.; Hanger, Jonathan; de Villiers, Deidre; Frère, Céline H.
Abstract: Effective conservation requires accurate data on population genetic diversity, inbreeding, and genetic structure. Increasingly, scientists are adopting genetic non‐invasive sampling (gNIS) as a cost‐effective population‐wide genetic monitoring approach. gNIS has, however, known limitations which may impact the accuracy of downstream genetic analyses. Here, using high‐quality single nucleotide polymorphism (SNP) data from blood/tissue sampling of a free‐ranging koala population ( n = 430), we investigated how the reduced SNP panel size and call rate typical of genetic non‐invasive samples (derived from experimental and field trials) impacts the accuracy of genetic measures, and also the effect of sampling intensity on these measures. We found that gNIS at small sample sizes (14% of population) can provide accurate population diversity measures, but slightly underestimated population inbreeding coefficients. Accurate measures of internal relatedness required at least 33% of the population to be sampled. Accurate geographic and genetic spatial autocorrelation analysis requires between 28% and 51% of the population to be sampled. We show that gNIS at low sample sizes can provide a powerful tool to aid conservation decision‐making and provide recommendations for researchers looking to apply these techniques to free‐ranging systems. Abstract : Genetic non‐invasive sampling is a powerful tool for monitoring free‐ranging populations. Here we test the accuracy of using non‐invasively sampled DNA for downstream individual and population level analysis. We find that non‐invasive genetic sampling can provide accurate genetic measures, depending on the questions being investigated.